Proposed relief map of the suitability of the Maranhão river Basin, Brazil, for anthropogenic use - Steinke, Valdir Adilson (2016)
In this paper, we proposed a method for mapping the suitability of land for intensive anthropogenic use in the Maranhão River Basin, in the state of Goiás, Brazil. We analyzed existing 1:250,000 maps of the local geology, drainage system topography and geomorphological features. We generated new information based on our analysis, including a compilation of basic morphometric data and a map of the slopes in the basin, which we used to construct the geomorphological suitability map of the watershed. Our results indicate that 40% of the study area can support intensive anthropogenic use; the remaining 60% of the basin area is categorized as “fragile” regarding the expansion of intensive land use.